Virtual chromoendoscopy for prediction of severity and disease extent in patients with inflammatory bowel disease: A randomized controlled study - Neumann, Helmut; Günther, Claudia; Neufert, Clemens; Kiesslich, Ralf; Grauer, Martin; Atreya, Raja; Neurath, Markus; Vieth, Michael (Inflammatory Bowel Diseases, 2013)
Background: Increased vascular permeability and angiogenesis play a crucial role in the pathogenesis of inflammatory bowel disease (IBD). Aim was to determine whether computed virtual chromoendoscopy has the potential to enhance assessment of disease severity and extent in patients with mild or inactive IBD in comparison to high-definition white-light endoscopy. Methods: Consecutive patients with IBD were randomly assigned at a 1:1 ratio to undergo colonoscopy with high-definition white light (group A) or computed virtual chromoendoscopy (group B). The mucosal vascular pattern and any mucosal abnormalities were recorded. Subsequent to endoscopic characterization targeted, biopsies were obtained from every segment for subsequent histopathological analysis of disease activity. Results: Overall, 100 patients were screened to participate in this study of whom 78 patients (high-definition white light, n = 39; computed virtual chromoendoscopy, n = 39) completed the study protocol thereby matching the previously calculated sample size. Average duration of the examination was 18 minutes in group A and 20.5 minutes in group B that was not statistically significant. When comparing the endoscopic prediction of inflammatory extent and activity with the histological results, an overall agreement of 48.71% and 53.85% (group A) and 92.31% and 89.74% (group B) was found, respectively. These differences were statistically significant (P = 0.0009 and P = 0.066). Conclusions: This study indicates that computed virtual chromoendoscopy significantly improves the diagnosis of the severity and extent of mucosal inflammation in patients with IBD. This newly developed imaging technique may therefore have important implications for therapeutic interventions in patients with IBD. Copyright © 2013 Crohn's & Colitis Foundation of America, Inc.
CRIS-Team Scopus Importer:2020-10-28
Keywords: Advanced imaging; Chromoendoscopy; Endocytoscopy; Endomicroscopy; FICE; I-scan; IBD; Mucosal healing; Prediction